Interleukin-1β, interleukin-6 and interleukin-10 polymorphisms in Tunisian patients with colorectal cancer and liver metastasis - Hazgui, Meriam; Weslati, Marwa; Ounissi, Donia; Boughriba, Rahma; Bacha, Dhouha; Yaacoubi Loueslati, Besma (Archives of Biological Sciences, 2022)
Paper description: Cytokines play an important role in cancer development. Understanding genetic disparities improves prognosis and establishes more reliable diagnostic tests. We investigated the expression and gene variants of IL-1β, IL-6 and IL-10 in colorectal cancer and liver metastases. The C/T genotype for IL-1β (-31C>T) increases colorectal cancer and liver metastasis risk; the C/A genotype for IL-10 (-592C>A) reduces both; the C/C genotype for IL-6 (-174G>C) increases liver metastasis risk. Cytokine expression and gene variants can serve as biomarkers for early detection of both colorectal cancer and liver metastases and help predict overall patient survival. Abstract: The balance between pro- and anti-inflammatory cytokine expression is essential for an efficient immune response and for the regulation of cancer development and progression. This study analyzed the expression and genetic variation in IL-1β, IL-6 and IL-10 genes and the possible associations with colorectal cancer (CRC) and colorectal liver metastases (CRLM).We examined IL-1β, IL-6 and IL-10 mRNA expression and three gene variants: IL-1β (rs1143627), IL-10 (rs1800872) and IL-6 (rs1800795), in 198 CRC, 65 CRLM patients and 230 controls. Carriers of the C/T genotype ofIL-1β (rs1143627) have an increased risk of developing CRC and CRLM. T/T genotype carriers have a higher risk of CRLM incidence. For IL-10 (rs1800872), patients harboring the C/A genotype have a lower risk of CRC and CRLM occurrence. For IL-6 (rs1800795), the C/C genotype heightens the risk of CRLM development. Overall survival analysis showed that carriers of the C/T genotype of IL-1β (rs1143627) have a worse overall survival in CRC patients. It can be concluded that interleukin genetic variants can be used as biomarkers to detect and predict clinical outcomes and prognostic factors for CRC and CRLM.